2017
DOI: 10.4103/ijmm.ijmm_17_257
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis B and Hepatitis C Virus Co-infection in India: A Systematic Review and Meta-analysis

Abstract: Hepatitis B virus (HBV) and hepatitis C virus (HCV) have several important similarities including worldwide distribution, hepato-tropism, similar modes of transmission and the ability to induce chronic infection that may lead to liver cirrhosis and hepatocellular carcinoma. Since both viruses are individually known to cause the pathologies mentioned above, co-infection with both HBV and HCV would be expected to be linked with higher morbidity as well as mortality and impact healthcare resource utilisation. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…The estimated prevalence of the coinfection of HIV and HBV (0.32%), HBV and HCV (0.32%), as well as HIV and HCV (0.32%) in this study, were consistent with the reported magnitude of coinfection from a recent systematic review [45,46]. However, the magnitude of the triple infection in this study (0.00%) was different from the reported magnitude of the global magnitude of triple infection 1.29% [45,46]. The lower number of participants as compared with the above studies could be the possible reason for the observed variation because of the rare nature of the occurrence of triple infection requiring the large sample size to estimate the magnitude.…”
Section: The Prevalence Of Chronic Viral Infections In People With Sesupporting
confidence: 90%
“…The estimated prevalence of the coinfection of HIV and HBV (0.32%), HBV and HCV (0.32%), as well as HIV and HCV (0.32%) in this study, were consistent with the reported magnitude of coinfection from a recent systematic review [45,46]. However, the magnitude of the triple infection in this study (0.00%) was different from the reported magnitude of the global magnitude of triple infection 1.29% [45,46]. The lower number of participants as compared with the above studies could be the possible reason for the observed variation because of the rare nature of the occurrence of triple infection requiring the large sample size to estimate the magnitude.…”
Section: The Prevalence Of Chronic Viral Infections In People With Sesupporting
confidence: 90%
“…[10] Among females, highest prevalence was found in age group of 51-60 (1.39%) years followed by 61-70 (1.15%) years and 41-50 (1.13%) years Similar results were noted by Patil et al and Quadri et al [13,14] In our study, co-infection of HBV and HCV was observed in 0.096% which was lower than that of Desikan et al (1.89%). [15] Of the total 214 HIV infected individuals included in our study, co-infection with HBV and HCV was found in 1.6% and 19.1% respectively. The higher prevalence rate of HCV in HIV positive patients in comparison to the rate for HBV positivity in HIV infected patients in our centre could be attributed to diverse factors such as increase in the rate of drug addiction, lack of vaccine for HCV.…”
Section: Discussionmentioning
confidence: 78%
“…Precise study is limited regarding co-infected patients. One study by Desikan et 11 al, from India reported 1.89% co-infected with both virus . Hepatitis B virus (HBV) and hepatitis C virus (HCV) have several important similarities including worldwide distribution, hepato-tropism, similar modes of transmission and the ability to induce chronic infection that may lead to liver cirrhosis and hepatocellular carcinoma.…”
Section: Datamentioning
confidence: 99%